Effects of crowding in the emergency department on the diagnosis and management of suspected acute coronary syndrome using rapid algorithms: an observational study. Issue 10 (8th October 2020) - Stoyanov, Kiril M; Biener, Moritz; Hund, Hauke; Mueller-Hennessen, Matthias; Vafaie, Mehrshad; Katus, Hugo A; Giannitsis, Evangelos
Abstract : Objectives: Fast diagnostic algorithms using high-sensitivity troponin (hsTn) in suspected acute coronary syndrome (ACS) are regarded as beneficial to expedite diagnosis and safe discharge of patients in crowded emergency departments (ED). This study investigates the effects of crowding on process times related to the diagnostic protocol itself or other time delays, and outcomes. Design: Prospective single-centre observational study. Setting: ED (Germany). Participants: Final study population of 2525 consecutive patients with suspected ACS within 12 months, after exclusion of patients with ST-elevation myocardial infarction, missing blood samples, referral from other hospitals or repeated visits. Interventions: Use of fast algorithms as per 2015 European Society of Cardiology guidelines. Main outcome measures: Crowding was defined as mismatch between patient numbers and monitoring capacities, or mean physician time per case, categorised as normal, high and very high crowding. Outcome measures were length of ED stay, direct discharge from ED, laboratory turn around times (TAT), utilisation of fast algorithms, absolute and relative non-laboratory time, as well as mortality. Results: Crowding was associated with increased length of ED stay (3.75–4.89 hours, p<0.001). While median TAT of the first hsTnT increased (53–57 min, p<0.001), total TAT of serial hsTnT did not increase significantly with higher crowding (p=0.170). Lower utilisation of fast algorithms (p=0.009) and increase of additional hsTnT measurements after diagnosis (p=0.001) were observed in higher crowding. Most importantly, crowding was significantly associated with prolonged absolute (p<0.001), and particularly relative non-laboratory time (63.3%–71.3%, p<0.001). However, there was no significant effect of crowding on mortality, even after adjustment for relevant clinical variables. Conclusions: Process times, and particularly non-laboratory times, are prolonged in a crowded ED diminishing some positive effects of fast diagnostic algorithms in suspected ACS. Higher crowding levels were not significantly associated with higher all-cause mortality rates. Trial registration number: NCT03111862 .